Detection of Galactomannan Antigen in the Serum of Iraqi Patients with Suspected Invasive Aspergillosis - Ali, Rawaa; Ali AL-Wattar, Wifaq M.; Jawad, Ali M. (Journal of the Faculty of Medicine Baghdad, 2016)
Invasive aspergillosis is a severe infection that occurs in patients with prolonged neutropenia, following chemotherapy,transplantation,or immunosuppressive protocols .Galactomannan ( GM) is a molecule ,found in the cell wall of Aspergillus species and is released in the blood during growth .The detection of GM in the blood is used to diagnose the invasive Aspergillosis in humans using ELISA assay.Objectives: To detect Galactomannan antigen in in the serum of immunocompramized patients suspected to have invasive aspergillosis.Patients and methods: This study was conducted on 50 patients from the hematology&oncology department,of Baghdad teaching hospital and pediatric oncology wards ,from March 2013 to October 2013.The patients presented with fever that is not responding to antibiotics along with cough and sputum and abnormal chest X-ray findings suspicious of IA. 11 healthy Iraqi individuals served as a control group.Results: ELISA test was positive in 39 of 50 (78%)while all of the control group individuals were negative(100%).The concentration of galactomannan antigen detected by ELISA was statistically significant when compared to control group( OD 0.658±0.033 vs 0.191±0.020 respectively) ( p